2018
DOI: 10.1002/art.40354
|View full text |Cite
|
Sign up to set email alerts
|

Germinal Center B Cells Are Essential for Collagen‐Induced Arthritis

Abstract: We identified GC formation and anticollagen antibody production as the key pathogenic functions of B cells in CIA. The role of B cells in RA is likely to be more complex. However, targeting the GC reaction could allow for therapeutic interventions that are more refined than general B cell depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Given the effect of WEHI‐112 in reducing CII‐specific IgG1 titers in CIA (Figure J), the importance of GCs for development of CIA , and the requirement for TBK‐1 in mediating ICOS signaling during Tfh cell maturation , we examined the GC response following WEHI‐112 treatment in the CIA model. Immunohistochemistry revealed an overall reduction in GC size as determined by GC area relative to total LN size (Figures A and B), although GC numbers were not affected by WEHI‐112 (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Given the effect of WEHI‐112 in reducing CII‐specific IgG1 titers in CIA (Figure J), the importance of GCs for development of CIA , and the requirement for TBK‐1 in mediating ICOS signaling during Tfh cell maturation , we examined the GC response following WEHI‐112 treatment in the CIA model. Immunohistochemistry revealed an overall reduction in GC size as determined by GC area relative to total LN size (Figures A and B), although GC numbers were not affected by WEHI‐112 (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…This is likely due to differences in cytokine skewing induced by these ligands. Finally, to investigate if the combination of IL-18 + αGalCer could support autoimmunity, we injected IL-18 alone or in combination with αGalCer in the collagen-induced arthritis (CIA) model of RA (30). We selected a protocol that has been shown to induce mild autoimmune arthritis (31) and found that the combination of IL-18 + αGalCer clearly enhanced the development of arthritis (Fig.…”
Section: Significancementioning
confidence: 99%
“…However, although CD4+ T cells are of essential significance for the induction and maintenance of inflammation in CIA and RA, the activation of self-antigen-specific B cells is thought to be extremely important for the target tissue damage 16 . The role of B cells in the pathogenesis of CIA, as in RA, is likely to be complex 17 .…”
mentioning
confidence: 99%
“…To corroborate the importance of antibodies in the pathogenesis of CIA are data indicating that the absence of B cells in genetically modified mice 19 and lowered number of B cells in mice treated with anti-CD20 antibodies 20 , inducing lack of CII-specific autoantibodies, protected mice against CIA 19 . The pathogenic role of B cells in CIA is mainly attributed to the secretion of anti-collagen antibodies 17 . The CII-specific autoantibodies are crucial for both the initiation and perpetuation of the clinical disease 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation